The Figure of the Criminal in Nineteenth-Century French Science and Literature (KULT_online, 2010)
Florian Beckerhoff’s monograph considers conflicting views of the criminal from nineteenth-century French science and literature. Monster und Menschen (Monsters and Men) portrays a fascination with a subject which scientists viewed as a threat to society, but which the literary world saw for its artistic potential. Beckerhoff explains how the figure of the murderer is depicted in fictional and scientific writings, and the extent of similarities in those texts attributed to both discourses. Of particular interest is the question of where these writings locate the killer on a spectrum ranging from man to monster. The author’s conclusion: the scientific understanding of the criminal is of a thinly disguised monster which is, ultimately, to be done away with; the literary evaluation, by contrast, is of a monstrous aspect of normal humanity.